Persepsi Penerapan Tenaga Kerja Terhadap Penerapan Sistem Manajemen Mutu Iso 9001:2015 Pada Proyek Konstruksi di Kabupaten Manokwari - Muhammad Sarifudin; Yoga C.V Tethool; Jamius Bin Stepanus (Green Publisher Indonesia, 2026)
This study highlights that uneven human resource quality can hinder the planning and execution of construction projects, making the implementation of a quality management system essential. The research aims to determine workers’ perceptions of the implementation of the ISO 9001:2015 Quality Management System in construction projects in Manokwari Regency. Data were collected using questionnaires and analyzed through descriptive qualitative statistical methods. Questionnaire results were tested for validity and reliability using data tabulation in Excel and manual processing with a rating scale. The analysis shows that the overall perception of ISO 9001:2015 implementation reached an achievement rate of 81.63%, categorized as Very Good. Among the perception indicators, the highest values were found in the customer satisfaction variable, specifically company commitment and company understanding (88.57%). In the leadership variable, responsibility and leadership control indicators achieved the highest score (90.00%). The involvement of people variable showed strong coordination (88.57%). For the process approach variable, identification indicators scored 86.67%. In continuous improvement, indicator development and method renewal reached 85.24%. Decision-making based on evidence was strongest in activity records (85.71%), while relationship management achieved its highest value in ensuring product and service quality (87.14%). Overall, the findings indicate that the ISO 9001:2015 Quality Management System has been implemented effectively in construction projects in Manokwari Regency, with particularly strong performance in leadership, customer satisfaction, and coordination aspects.